Data Protection in Employment: Implications of the Personal Data Protection Act in Tanzania - Mark Malekela; Aliko Simon (Labour & Law Issues)
Innovations in technology, their varied uses, and the widespread use of social media have all advanced more quickly than in the past, both globally and in the workplace, where employee and customer data is constantly being collected and digitally documented. For this reason, the need for regulatory compliance on protecting personal data in the workplace is paramount. Based on critical analysis of the relevant legislation, case laws, and literature, this article reviews the current state of privacy and data protection in the employment context in Tanzania. This article discusses the implications of the new data protection legislation in Tanzania with a focus on privacy and data protection rights and employee monitoring issues that human resource professionals, managers and employers must be aware of. As it is common for employers to keep employment records, which amount to data, employment is one of the numerous areas and facets in Tanzania that are impacted by the PDPA, 2022. In accordance with the PDPA, employers have a responsibility to protect employee data as data controllers who process sensitive personal data to satisfy the condition that the processing is necessary for the purposes of compliance with the ELRA. Finally, this article recommends that like the EU’s W29 opinion on protection of employee personal data, a special guidance note tailored on employee personal data protection from the PDPC will improve employee privacy in Tanzania.